Regenerative endodontics: integrative review (Research, Society and Development, 2022)
Endodontics is the branch of dentistry that studies the pulp and its periradicular tissues, with the aim of preventing, diagnosing and treating its various diseases. With the advance in the principles of regenerative endodontics, new protocols have emerged to regenerate and preserve the pulp tissue that was once lost. Among the various techniques studied in regenerative endodontics, we highlight cell therapy, a protocol that has been little studied in the literature. The aim of this review was to investigate the feasibility of pulp regeneration techniques using dental pulp stem cells, highlighting their advantages, disadvantages, clinical efficacy, indications and limitations. An integrative literature review was conducted by searching scientific articles in the electronic databases PubMed, Medline, Scopus and Web of science using the descriptors: pulp, regeneration, transplant, indexed in the period from 2017 to 2022. After the eligibility criteria, 14 studies were selected entirely in the English language. The studies showed the feasibility of cell culture techniques, as well as their excellent clinical results, with thickening of root walls, regression of lesions and positive response to sensitivity tests. However, the techniques have high financial, operational and laboratory costs for their development, and there is a lack of clinical trials to establish a clinical protocol.